If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(2x + -9) = 15 Reorder the terms: 3x(-9 + 2x) = 15 (-9 * 3x + 2x * 3x) = 15 (-27x + 6x2) = 15 Solving -27x + 6x2 = 15 Solving for variable 'x'. Reorder the terms: -15 + -27x + 6x2 = 15 + -15 Combine like terms: 15 + -15 = 0 -15 + -27x + 6x2 = 0 Factor out the Greatest Common Factor (GCF), '3'. 3(-5 + -9x + 2x2) = 0 Factor a trinomial. 3((-1 + -2x)(5 + -1x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-1 + -2x)' equal to zero and attempt to solve: Simplifying -1 + -2x = 0 Solving -1 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -2x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -2x = 0 + 1 -2x = 0 + 1 Combine like terms: 0 + 1 = 1 -2x = 1 Divide each side by '-2'. x = -0.5 Simplifying x = -0.5Subproblem 2
Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5Solution
x = {-0.5, 5}
| (q+4)(3q-15)=0 | | (w+8)(-11)= | | x(x-24)=0 | | 6y+6=8y | | -2x+58=-8 | | 7y-6(5y-6)=0 | | 36w^2-16=0 | | 4y+12=5y | | 32+y=40 | | 5x^2-36x+7=0 | | x-14=-38 | | 9x^2-3x-20=0 | | 6+2w=42 | | z^2-z-20=0 | | x^2+11x-28=0 | | 20=c(c-8) | | 7y+-2x=5 | | 14s^2-33s+18=0 | | 4a^2+15-16a=0 | | 72=-8(4x-5) | | 4b^2-2=322 | | 5m=13 | | 8x^2-3x+2=7x^2 | | 7x+-2y=5 | | 500=9w+2l | | 5-3x=5x-11 | | z^4-37z^2+36=0 | | x-8=4-x | | 42y^2-69y+20=7y^2-8 | | 120=5l+2w | | 20t^2-39t+18=0 | | 6c-9c+14=20 |